La escolástica española y su teoría de la justicia: el caso de Luis de León. - CONTRERAS, SEBASTIÁN (Bulletin of Hispanic Studies (1475-3839), 2014)
In this paper, the author aims to review the doctrine of justice of Luis de León, a major writer on Spanish thought. Since its inception, with the teaching of Fran-cisco de Vitoria, the Spanish School of natural law led the way in the development of theology and philosophy in the Thomist tradition. In the construction of this new philosophy of justice, the ideas of Leon have been particularly relevant. From literature and mysticism, his theology of the law has become one of the pillars of the history of law.